PENGUATAN PERAN KADER BINA KELUARGA BALITA MENUJU KAMPUNG KB (COE) DI PUCANGSAWITSURAKARTA STRENGTHENING THE ROLE OF CHILDHOOD FAMILY DEVELOPMENT CHADDREN TOWARDS KAMPUNG KB (COE) IN PUCANGSAWIT SURAKARTA - Widayati, Rina Sri; Sari, Dewi Kartika (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
The problem of the lack of public knowledge about the basic needs of new born babies is something that must be considered. With optimal fulfillment, it can improve the health of the baby which becomes a golden start for the next stage. The Kampung KB container in Pucangsawit is the right tool for optimizing activities involving the community through the BKB, BKR, BKL, UPPKS, Priyoutomo, Environmental PKB, Integrated Posyandu, Elderly Post, Family Planning Services, with community empowerment activation activities so that they are able to strengthen BKB cadres become Center of Excellent. Efforts to establish a training center for Omah kriya si Pucang became an innovation in the priority of this activity. Methods ranging from FGD, outreach, training and mentoring so that BKB cadres obtain comprehensive material. An educational approach to all communities, religious leaders, community tokogs, and stakeholders is the main concern in this activity. Activities carried out in May and continued with community assistance so that they are able to monitor and evaluate activities. The results of activities in the correct breastfeeding technique training resulted in an increase in knowledge by 35% from before the training, while the KMC method was able to increase the ability to simulate the method by 45% from before the simulation. Training and mentoring for basic needs training for newborns can increase the knowledge and ability of cadres to practice these activities.